Social Relevance of Alembamento in the Ambundu Culture in Malanje: https://doi.org/10.60543/ts_iss.vi6.9403 ("Temas Sociais" Journal, 2024)
This article sought to understand the theme of the social relevance of alembamento in the ambundu culture in Malanje. To this end, qualitative data from participants relating to the research were researched and analyzed. Therefore, it seeks to telegraphically substantiate the changes that ocurred in the practice of alembamento as a social institution of the ambundu peoplo, as well as its effects talking into account the abandonment of their traditional rites. From its analysis, it was found that, alembamento is the marriege itself in this culture, covered with immense rites of passage that guarantee its social legitimacy, as its social relevance aims to unite and honor families. However, the neutralization of the initiation process, the figure of the uncle and aunt and the non-legalization in the Angolan legal system, are factors that influence the changes registered today in the practice of alembamento and its social trivialization.